2004
DOI: 10.1002/rcm.1508
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cyclophosphamide and its metabolites in urine using liquid chromatography/tandem mass spectrometry

Abstract: A reliable and easy to use liquid chromatography/tandem mass spectrometry (LC/MS/MS) method was developed for the simultaneous quantification of urinary concentrations of cyclophosphamide (CP) and its main metabolites excreted in urine, i.e. N-dechloroethylcyclophosphamide (DCL-CP), 4-ketocyclophosphamide (4KetoCP), and carboxyphosphamide (CarboxyCP). Sample preparation consisted of dilution of urine with an aqueous solution of the internal standard D 4 -CP and methanol, and centrifugation. LC/MS/MS detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…Thus, highly sensitive analytical methods for determination of CP in plasma and urine were developed and validated regarding LOD, precision and stability. The LODs in this study were lower compared to previous methods for determination of CP in plasma (Sadagopan et al 2001;Liu et al 2004) and urine Sannolo et al 1999;Pethran et al 2003;Kasel et al 2004). The precisions of our methods were satisfactory and the stability of CP in the samples was high.…”
Section: Discussioncontrasting
confidence: 61%
“…Thus, highly sensitive analytical methods for determination of CP in plasma and urine were developed and validated regarding LOD, precision and stability. The LODs in this study were lower compared to previous methods for determination of CP in plasma (Sadagopan et al 2001;Liu et al 2004) and urine Sannolo et al 1999;Pethran et al 2003;Kasel et al 2004). The precisions of our methods were satisfactory and the stability of CP in the samples was high.…”
Section: Discussioncontrasting
confidence: 61%
“…4B. Although the present method is an extremely simple analytical method which does not require even deproteinization, it was possible to measure with extremely high sensitivity compared with the method reported previously [4][5][6]. The results of stability test are summarized in Table 2.…”
Section: Hplc Methods Development and Validationmentioning
confidence: 86%
“…This suggested that medical staff could be exposed to these sources in situations other than drug preparation and administration. In 2004, Kasel et al [6] reported an analytical method using liquid chromatography/tandem mass spectrometry (LC/MS/MS) to quantify the concentrations of cyclophosphamide (detection limit: 5 ng/mL) and its metabolites, N-dechloroethylcyclophosphamide, 4-ketocyclophosphamide, and carboxyphosphamide, in urine. Although the method was reliable compared to the traditional GC/MS method, it was unable to detect trace amounts of cyclophosphamide in the urine of occupationally exposed medical staff.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods either described the quantification of CP and other metabolites in urine [2,3] or quantification of 4OHCP without CP in human plasma [4]. Sadagopan described the simultaneous quantification of CP and 4OHCP in mouse plasma [5].…”
Section: Introductionmentioning
confidence: 98%
“…Assays quantifying CP and/or 4OHCP using highperformance liquid chromatography (HPLC) with mass spectrometry (MS) detection have been described previously [2][3][4][5][6]. However, these methods either described the quantification of CP and other metabolites in urine [2,3] or quantification of 4OHCP without CP in human plasma [4].…”
Section: Introductionmentioning
confidence: 99%